2019
DOI: 10.1111/liv.14234
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma circulating microvesicles in patients with HCV‐related cirrhosis after treatment with direct‐acting antivirals

Abstract: Background & Aims The eradication of Hepatitis C (HCV) infection by direct‐acting antiviral (DAAs) agents has been linked to an amelioration of liver synthesis and regression of fibrosis. Although changes in number and type of circulating microvesicles (MVs) have been reported in cirrhosis, conclusive data on the effect of DAAs treatment on MVs profile in HCV cirrhotic patients remain scarce. Methods We measured the levels of endothelial, platelet and hepatocyte MVs, as well as MVs‐expressing versican core pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…These studies are discussed in the supplementary text. 39,47,125,126,135,[138][139][140][141][142] Prediction of mortality In a prospective collaborative study, including a validation cohort, we demonstrated that plasma levels of hepatocyte-derived extracellular vesicles can predict 6-month mortality, independently of Child-Pugh and MELD scores, using a threshold of 65 IU/L. 40 In this study, other subpopulations of plasma extracellular vesicles, including panleukocyte (CD11+) and endothelial (CD144+, CD62E+), were not useful for predicting mortality.…”
Section: Prediction Of Complications Of Cirrhosismentioning
confidence: 72%
“…These studies are discussed in the supplementary text. 39,47,125,126,135,[138][139][140][141][142] Prediction of mortality In a prospective collaborative study, including a validation cohort, we demonstrated that plasma levels of hepatocyte-derived extracellular vesicles can predict 6-month mortality, independently of Child-Pugh and MELD scores, using a threshold of 65 IU/L. 40 In this study, other subpopulations of plasma extracellular vesicles, including panleukocyte (CD11+) and endothelial (CD144+, CD62E+), were not useful for predicting mortality.…”
Section: Prediction Of Complications Of Cirrhosismentioning
confidence: 72%
“…Circulating MPs were assayed by flow cytometry (Cytoflex, Beckman Coulter, Pasadena, CA, USA), as described previously [ 3 , 17 ]. Total MPs were identified by their dimensional features using beads of specific diameters with conformational characteristics resembling those of MPs (Megamix SSC-fluorescent beads [0.16, 0.24, 0.5, 0.9 and 3 μm]), and labeling them with monoclonal anti-annexin V conjugated with Fluorescein isothiocyanate (FITC- Bender Med Systems GmbH, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular vesicles are nanosized particles shed into body fluids by many cell types that carry various bioactive molecules; among them, plasma microvesicles (100–1000 nm in size) are key messengers of cellular communication. Enhanced microvesicle levels were linked to disease activity and progression, e.g., microvesicles isolated from patients with HCV-related decompensated cirrhosis induce vascular hypocontractility, contributing to portal hypertension and circulatory dysfunctions [ 164 ]. Versican-positive microvesicles were found elevated in patients with HCV-induced cirrhosis, and further increased with HCC [ 103 ].…”
Section: Liver Fibrosis and Cirrhosismentioning
confidence: 99%
“…Versican-positive microvesicles were found elevated in patients with HCV-induced cirrhosis, and further increased with HCC [ 103 ]. In patients who had received DAAs, the levels of versican-positive microvesicles dropped at the end of treatment and remained low throughout the 48-week follow-up [ 164 ]. This supports the view that DAA-induced eradication of HCV could promote a reversal of fibrosis, and versican-positive microvesicles could be a potential early biomarker of liver fibrosis.…”
Section: Liver Fibrosis and Cirrhosismentioning
confidence: 99%